Bioaccumulation and in vivo formation of titanium dioxide nanoparticles in edible mussels. (1st September 2020) - Gallocchio, Federica; Biancotto, Giancarlo; Moressa, Alessandra; Pascoli, Francesco; Pretto, Tobia; Toffan, Anna; Arcangeli, Giuseppe; Montesi, Francesco; Peters, Ruud; Ricci, Antonia
Highlights: Edible mussels can accumulate TiO2 NPs if kept in water contaminated by TiO2 NPs. TiO2 NPs can also be found in mussels kept in water contaminated by ionic Ti. Potential in vivo formation of TiO2 NPs occurs in mussels. Mussels can eliminate more than 70% of TiO2 NPs after 3 days' depuration. Non-depurated mussels may be a source of exposure to NPs for consumers. Abstract: The aim of this study was to evaluate the bioaccumulation of titanium dioxide nanoparticles (TiO2 NPs) in edible mussels bred in polluted artificial seawater. An in vivo study was conducted by exposing mussels to different concentrations of TiO2 NPs (0.25 mg/L and 2.5 mg/L) or ionic titanium (1.6 mg/L) for 4 days. Inductively coupled plasma mass spectrometry (ICP-MS) showed titanium presence in all groups proportional to exposure levels (concentration range: 209–1119 µg/kg). Single particle ICP-MS revealed NPs in both TiO2 NP treated mussels (concentration range: 231–1778 µg/kg) and in ionic titanium treated mussels (concentration 1574 µg/kg), suggesting potential nanoparticle formation in vivo . These results were confirmed by transmission electron microscopy with energy dispersive X-ray detection. Nonetheless, mussels eliminated more than 70% of the TiO2 NPs after 3 days' depuration. These results show the potential for consumer exposure to TiO2 NPs when contaminated mussels are consumed without a proper depuration process.